Influência nutricional na produção de sementes de tomate em cultivo protegido - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The tomato BRS Nagai is a hybrid developed by Embrapa, whose growth habit is indeterminate, adapts in any tomato producing region of Brazil, has desirable agronomic characteristics, among them resistance and/or tolerance to 40 variants of races of pathogens. In spite of these advantages present in the hybrid in commercial crops, this cultivar during the seed production phase presents little seed yield. Thus, it is a challenge for the study to investigate the influence of some factors, among them, the nutritional aspect in seed production. Nutrition is a key factor for the development of plants in physiological and morphological aspects, contributing to plant formation. In the tomato production chain, the seed has a high importance, corresponding to up to 8% of the total cost of production, and in the case of hybrid seeds, because manual pollination is used, the cost is even higher. Therefore, some aspects are important for seed production technology, among these of seed production, among these factors includes nutrition and plant fertilization. Although the relationship of nutrient effect on seed production is poorly studied, the objectives of this work were to evaluate the nutritional influence on the production of tomato seeds, BRS Nagai hybrid, in protected cultivation as well as fertilization interference on seed quality. For this, manual pollination was done between the male parental (LAM 156) and the female parental (LAM147) for hybrid production and later, harvest and seed extraction. Zinc (Zn), Boron (B) and Humic Acid (AH) were applied to the female parental plants at the time of flowering, with the flowers being emasculated in preanthesis for manual pollination and hybrids identification. To verify the influence of fertilization on seed quality, it was necessary to perform the chemical characterization test of the seeds to know the content of nutrients absorbed. In the experiment, the seed yield and the physiological quality of the seeds were evaluated. Based on the results obtained in this study, it was observed that the use of humic acid only favors the production and quality of the seeds and that B showed positive effects with humic acid, unlike Zn that had results without humic acid.
Keywords: Solanum lycopersicum; BRS Nagai; nutrição de plantas; rendimento de sementes; influência nutricional; qualidade fisiológica; Solanum lycopersicum; BRS Nagai; plant nutrition; seed yield; nutritional influence; physiological quality; CIENCIAS AGRARIAS